2019
DOI: 10.13004/kjnt.2019.15.e35
|View full text |Cite
|
Sign up to set email alerts
|

The Clock Is Ticking – Brain Atrophy in Case of Acute Trauma?

Abstract: ObjectiveBrain atrophy and brain herniation are gaining a lot of attention separately, but a limited amount of studies connected them together, and because of this, we are going to review and examine the subject in the current meta-analysis.MethodsThe authors collected data reporting brain atrophy of alcoholic and schizophrenic cause, as well as data on control patients, all of which was published on MEDLINE between 1996 and 2018. The included 11 articles were processed with a statistical program.ResultsWe fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Additionally, even though it has been suggested that certain anatomical or physiological differences in younger children’s metabolism might make them more prone to severe primary or secondary brain injury compared to adults, the prognostic value of age as a predictor of poor outcome has not yet been confirmed, similarly to our findings [ 49 , 50 ]. An interesting recent report has connected the clinical or prognostic differentiations of TBI patients with anatomic variations among ethnicities or sexes or with age-related atrophy, which could account for time-delays in symptomatology of IC-HTN in certain individuals [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even though it has been suggested that certain anatomical or physiological differences in younger children’s metabolism might make them more prone to severe primary or secondary brain injury compared to adults, the prognostic value of age as a predictor of poor outcome has not yet been confirmed, similarly to our findings [ 49 , 50 ]. An interesting recent report has connected the clinical or prognostic differentiations of TBI patients with anatomic variations among ethnicities or sexes or with age-related atrophy, which could account for time-delays in symptomatology of IC-HTN in certain individuals [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had a sizable hematoma, but the symptoms were not severe for the last 2.5 months, and the patient's brain atrophy was seen on CT of the brain. This can be explained in two ways, one is because the brain parenchyma atrophy should reduce the space-occupying effect caused by the hematoma, 12 the other is because the brain of this patient has a good adaptation to the hematoma. However, when the blood mass increases rapidly, it causes hemiplegia symptoms, affecting the patient's daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgery is an especially technologically advanced discipline which is constantly developing over time; uniquely, the establishment of surgery on the brain and CNS followed breakthroughs in microbiology and anesthesia, and understandings of ventricle and cerebral vascular anatomy, and head trauma [90,91]. The culmination of advancements in neuroscience, surgery, and technology have allowed for significant breakthroughs in neurosurgery (e.g., DBS, awake craniotomy, focused ultrasound, etc.…”
Section: How Innovation Could Be Advanced In Neurosurgerymentioning
confidence: 99%